2014
DOI: 10.11607/jomi.3729
|View full text |Cite
|
Sign up to set email alerts
|

Implant Survival Rate and Marginal Bone Loss of 6-mm Short Implants: A 2-Year Clinical Report

Abstract: This 2-year study illustrated that short implants are a viable option in selected clinical scenarios. Short implants with wider diameters are preferred because they have less marginal implant bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Several reports show implant length has no impact on peri‐implant MBL in the short term 65–67 . However, it seems reasonable to assume that peri‐implant bone loss around short implants can be more critical than in standard implants, as loss of osseointegration can occur in a short time span 65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports show implant length has no impact on peri‐implant MBL in the short term 65–67 . However, it seems reasonable to assume that peri‐implant bone loss around short implants can be more critical than in standard implants, as loss of osseointegration can occur in a short time span 65 .…”
Section: Discussionmentioning
confidence: 99%
“…24,27 Several reports show implant length has no impact on peri-implant MBL in the short term. [65][66][67] However, it seems reasonable to assume that peri-implant bone loss around short implants can be more critical than in standard implants, as loss of osseointegration can occur in a short time span. 65 Therefore, it is crucial to control main risk factors for peri-implant diseases and apply strict maintenance programs for long-term performance of these implants.…”
Section: Discussionmentioning
confidence: 99%
“…Implant features might have favored results of the present study. Few findings have been reported in recent literature on MBL around short implants . Reported results of MBL around short implants do not exceed the criteria accepted for standard implants (i.e., 1.5 mm for the first year and 0.2 mm of additional bone loss each subsequent year).…”
Section: Discussionmentioning
confidence: 85%
“…Few findings have been reported in recent literature on MBL around short implants. 7,[35][36][37][38][39] Reported results of MBL around short implants do not exceed the criteria accepted for standard implants (i.e., 1.5 mm for the first year and 0.2 mm of additional bone loss each subsequent year). It should be noted that 3 years after loading, almost 2 mm of bone loss around a 6.5 mm implant corresponds to nearly one third of the entire implant length and should be interpreted differently on clinical grounds.…”
Section: Discussionmentioning
confidence: 98%
“…In this light, the authors started using so-called short implants [6][7][8][9], in order to avoid preimplant surgeries dedicated to recreating bone volumes after the resorption process that follows every extraction [10,11]. The clinical results using these implants showed that specific biomechanical constraints facing short implants did not affect their prognosis [12,13] and even lead to less bone resorption and less complications than longer implants placed in vertically augmented bone graft sites [14]. This may extend indications for implant sites with reduced bone height.…”
Section: Introductionmentioning
confidence: 99%